The cell wall-associated kinases, WAKs, as pectin receptors - Kohorn, Bruce D.; Kohorn, Susan L. (Frontiers in Plant Science, 2012)
The Wall Associated Kinases, WAKs, are encoded by 5 highly similar genes clustered in a 30 kb locus in Arabidopsis. These receptor-like proteins contain a cytoplasmic serine threonine kinase, a transmembrane domain, and a less conserved region that is bound to the cell wall and contains a series of Epidermal Growth Factor (EGF) repeats. Evidence is emerging that WAKs serve as pectin receptors, for both short oligogalacturonic acid fragments (OGs) generated during pathogen exposure or wounding, and for longer pectins resident in native cell walls. This ability to bind and respond to several types of pectins correlates with a demonstrated role for WAKs in both the pathogen response and cell expansion during plant development.